Comparison of Muscle Energy Technique versus Kinesio Taping Technique to Reduce Pain and Improve Lower Limb Functional Activity in Patients with Plantar Fasciitis (Medical Forum Monthly, 2022)
Objective: To compare the effectiveness of muscle energy techniques versus calcaneal taping for reducing pain and Improve Lower limb Functional Activity in Patients with Plantar Fasciitis.Study Design: Randomized clinical trial studyPlace and Duration of Study: This study was conducted at the Haq Orthopaedic Hospital and Surraya Azeem Hospital, Lahore from July, 2018 to July, 2019 for a period of one-year.Materials and Methods: Through non-probability convenient sampling technique 52 Subjects were recruited and allocated in two groups by using Lottery method of Randomization. Subjects diagnosed having plantar fasciitis for more than 6 months and age between 20-60 years were included in study. Those with any foot surgery or neurological deficit or with any referred pain to foot were excluded from the study. Group A received taping along with conventional treatment group B received MET along with Conventional physiotherapy protocol (therapeutic ultrasound, foot intrinsic muscles’ strengthening exercises, TA stretching exercise). Total 7 sessions were given on alternate days with each session for about 30 minutes. Assessment was done prior to (pre) and at the end (post) of treatment through Visual Analogue Pain Scale (VAS) and Foot Function Index (FFI).Results: The total mean±SD of total score of post treatment FFI was 13.5296±5.25312 for group A and 21.2712±9.30238 for group B with p value of 0.001. The pain measured on the VAS showed mean± SD of 1.42±0.758 for group A and 2.92±1.354 for group B with p-value of 0.000. Paired t-test shows p-value of 0.000 which is highly significant.Conclusion: Taping is more effective than muscle energy techniques to reduce pain and improve lower limb functional activity when given along with conventional physiotherapy protocol.